Environmental pollution & toxicology - Joshi, B.D.; Joshi, P. C.; Joshi, Namita; Indian Academy of Environmental Sciences (New Delhi : A.P.H. Pub. Corp., 2008)
Contributed seminar articles organized by Indian Academy of Environmental Sciences, Hardwar
Includes bibliographical references